“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)
Publisher: University of Illinois Press

Revitalising language through music: a case study of music and culturally grounded pedagogy in two Kanien’ke:ha (Mohawk) language immersion programmes - Vallejo, Jessie M. (Ethnomusicology Forum, 2019)
Since the 1990s scholars, teachers, and policy makers have debated over the importance of culturally grounded or culture-based education (CBE) approaches in primary and secondary programmes. For Indigenous communities, CBE methods are often regarded as decolonising tools that support linguistic and sociocultural revitalisation efforts. A majority of Indigenous educational projects have prioritised teaching language above other cultural components, such as music, which has largely been overlooked as a powerful tool due to the pervasive assumption that traditional musical practices rely on the language to survive. This article explores how cultural components have a symbiotic rather than a hierarchical relationship, focusing on the interdependence between language and music. Based on ethnographic fieldwork and observations with four Indigenous language immersion teachers, I argue that music is a linchpin pedagogical tool that promotes intergenerational interactions, builds social relationships, and facilitates the daily use of language in and outside the classroom.
Keywords: Haudenosaunee; Indigenous; Iroquois; culture-based education; decolonisation; language immersion